Development of chia plants in field conditions at different sowing-date - Goergen, Patrícia Carine Hüller; Lago, Isabel; Scheffel, Lúcio Gabriel; Rossato , Ioran Guedes; Roth, Gabriel Felipe Maboni; Durigon, Angelica; Pohlmann, Valeria (Comunicata Scientiae, 2022)
The objective of this study was to characterize the development of chia plants sown at different dates, and to determine the relation between the duration of the development cycle and the final number of leaves and the leaf appearance rate on the main stem. A field experiment was conducted in the agricultural year of 2016/2017 in five sowing dates (09/22/16, 10/28/16, 01/03/17, 02/08/17 and 03/24/17) in the edaphoclimatic conditions of the central region of the RS, Brazil. A randomized block design with four replicates was used. For each sowing date, the duration of the vegetative and reproductive phases in days and in °C day (Tb = 11 °C), the final number of leaves and the phyllochron of the main stem were determined. The duration of the vegetative phase of chia plants in days and in ºC day varies between the sowing dates, with shorter duration in late sowings in response to the photoperiod reduction. The vegetative phase represents the largest part of the total development cycle in early sowing dates, being overcome by the reproductive phase in late sowing dates (02/08/17 and 03/24/17). The phyllochron for chia varies from 36.23 (very late sowing) to 59.88 ºC day (early sowing). Later sowing has a smaller final number of leaves accumulated in the main stem due to the shorter duration of the vegetative phase.